2020
DOI: 10.1159/000508963
|View full text |Cite
|
Sign up to set email alerts
|

A Genomic Test for Colorectal Cancer Risk: Is This Acceptable and Feasible in Primary Care?

Abstract: Introduction: Genomic tests can predict risk and tailor screening recommendations for colorectal cancer (CRC). Primary care could be suitable for their widespread implementation. Objective: We aimed to assess the feasibility and acceptability of administering a CRC genomic test in primary care. Methods: Participants aged 45-74 years recruited from 4 Australian general practices were offered a genomic CRC risk test. Participants received brief verbal information about the test comprising 45 CRC-associated singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…3 Research examining preferences for a cancer PRS have focused on single cancer types. 13,19,26,34 Our study is the first to examine how cancer type, as well as a multicancer PRS test, are traded off when choosing between alternative PRS testing approaches. Results from the MXL model showed a preference for a multicancer test and cancer types including breast cancer, prostate cancer, and bowel cancer whereas no significant preference was found for pancreatic cancer, lung cancer, or melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Research examining preferences for a cancer PRS have focused on single cancer types. 13,19,26,34 Our study is the first to examine how cancer type, as well as a multicancer PRS test, are traded off when choosing between alternative PRS testing approaches. Results from the MXL model showed a preference for a multicancer test and cancer types including breast cancer, prostate cancer, and bowel cancer whereas no significant preference was found for pancreatic cancer, lung cancer, or melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is acceptable to specialist clinicians, there is mixed evidence as to whether this will be acceptable to patients. 14,18,19 Additional variables of concern to the public include privacy protections and the potential impact of genomic test results on life insurance plans. 12,13,16,20 Despite the importance of understanding public preferences regarding PRSs, there is a lack of data to adequately understand how these variables are traded off and the subsequent impact on implementation.…”
Section: Introductionmentioning
confidence: 99%
“…PRS information could motivate risk-reducing health behavior, for example by prompting initiation of medication, screening, or lifestyle changes 27 . Although not focused on PRSs specifically, research on inherited cancer syndromes has shown improved screening adherence following disclosure of genetic test results 28 . Additionally, a recent study suggested that providing people with personal genetic results about obesity risk can alter cardiorespiratory and satiety physiologies, including perceived exertion and running endurance during exercise and perceived fullness after food consumption 29 .…”
Section: Slowing Disease Progression and Recurrencementioning
confidence: 99%
“…Online communication of genomic results has not been explored in the clinical setting to date and development of a theoretical-based, online communication framework would be required to ensure a decision-empowered informed consent process. Work in other salient areas, including dynamic consent processes, 35 the role of GPs in polygenic risk assessments, 36 and a self-sampling approach to tissue collection, 37 are already in progress and look promising. A major policy decision that will affect the clinical efficacy and cost effectiveness of risk stratification is the age at which the risk assessment is offered.…”
Section: Discussionmentioning
confidence: 99%